Splendors and glooms - Schlitz, Laura Amy (Candlewick Press, 2012)
When Clara vanishes after the puppeteer Grisini and two orphaned assistants were at her twelfth birthday party, suspicion of kidnapping chases the trio away from London and soon the two orphans are caught in a trap set by Grisini's ancient rival, a witch with a deadly inheritance to shed before it is too late.